Delightful Heirlooms Goings Under The Hammer - New Straits Times, Elizabeth John (2008)
Ruby-enrusted heirlooms and old gamelan sets that apparently sound their own music at night are among items in a 4,000-piece collection of antiques that go under the hammer today.